Tasamuh versus tolerance as practical approach to encounter the conflicting issue - Ruhaizah Abdul Ghani; Jaffary Awang (Penerbit Universiti Kebangsaan Malaysia, 2020)
Tasamuh is a concept introduced in Islam and was practiced during the time of Prophet Muhammad SAW. Its concept and practice was proved to be the realistic and practical concept in the multi religious society during his period. Even several centuries after the prophetic time, Tasamuh was also substantiated as good practice of Muslim society towards non-Muslims as to ensure social harmony with regard to sensitive religious issues. Changing of time created life to be more complicated and formed more pluralistic societies. The pluralities of religions and cultures require a fit solution to settle any conflicting issues arose. In this case, much discussion on the concept of tolerance took place compared to the concept of Tasamuh. This paper means to grasp the meaning of Tasamuh and tolerance from their roots either grounded for the sources or resulted from the history of the society. By using method of content analysis of the references that related to Tasamuh and tolerance, the paper explores the meaning of both words as well as the factors that formed the terminological meanings of Tasamuh and tolerance. The paper further presents the comparison and contrast of both concepts from several angles. As a result, this paper decides that Tasamuh or suggested as Islamic tolerance to be more comprehensive concept which can be practiced to deal with the differences in pluralistic society.